(3GdJONd GdOhdj GdEfSGfj (B/ s - (3hGFd hfjS Ydj YeQs; (3YGFTI QGJH s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2010)
(3NdUJ GdOQGSI Edi fJjLI eaGOgG Cf YOe EMJQGe GdbhGfjf hGdehGKjb GdOhdjI hdGSjeG Jdc GdeJYdbI HEMJQGe GdEfSGf hcQGeJg hMbhbg hhLhOg abO aJM GdHGH Ydi eUQGYjg GeGe EfJgGc eHOC GdSjGOI GdhWfjI heHOC YOe ESJNOGe GdbhI GdYScQjI aj GdYdGbGJ GdOhdjI hef gfG cGfJ GdMGLI GdedMI HVQhQI EdJRGe GdfXe GdOhdjI GdeNJdaI HGdTQYI GdOhdjI dMbhb GdEfSGf hGdbGfhf GdOhdi GdEfSGfj hPdc HYOe EQJcGH GdLQGFe GdOhdjI hEMJQGe cQGeI GdEfSGf hef LgI CNQi VQhQI GYdGA cdeI GdbGfhf GdOhdj hEUdGM gjcdI GLgRI GdCee GdeJMOI HeG jfSLe eY eHGOiA GdeSGhGI hGdYOGdIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb, (B2010(3, bSe GdbGfhf GdOhdjs
(3HHdjhLQGajG(B: (3UaMGJ (B268-278s
Keywords: (3GdbGfhf GdOhdj GdEfSGfjs; (3GdbGfhf GdOhdj dMbhb GdEfSGfs; (3MeGjI QYGjG GdOhdIs; (3eHOC YOe GdJONd s; (3Mbhb GdEfSGfs; (3GdJONd GdYScQjs; (3GdeLGd GdeMahXs; (3GfJgGcGJ Mbhb GdEfSGfs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs